THEORETICAL PRINCIPLES OF REGIONAL DEVELOPMENT IN MODERN CONDITIONS - Dziundziuk V.B.; Cherniak М.Ye. (Pressing Problems of Public Administration, 2017)
The evolution and main modern approaches to the analysis of regional development and its essentialcharacteristics are considered. It is proved that in the science and practice of public administrationthere is no single, common de nition for regional development. It is shown that the de nition ofdevelopment and its directions is always geographically differentiated, and may change over time. Itwas established that in the 21st century, there was a deviation from economic determinism in de ningregional development, and today the concept of ‘development’ is considered in terms of the need totake into account social, environmental, political, cultural, and other factors. It has been revealed thatthe process of managing territorial development should be carried out by various stakeholders, andtheir relations should be based on partnership and dialogue.